The borehole dilatometer network of Mount Etna: A powerful tool to detect and infer volcano dynamics. Issue 6 (23rd June 2016) - Bonaccorso, A.; Linde, A.; Currenti, G.; Sacks, S.; Sicali, A.
Abstract: A network of four borehole dilatometers has been installed on Etna in two successive phases (2010–2011 and 2014). The borehole dilatometers are installed in holes drilled at depths usually greater than 100 m, and they measure the volumetric strain of the surrounding rock with a nominal precision up to 10 −11 in a wide frequency range (10 −7 –25 Hz). Here we describe the characteristics of the network and the results of the in situ calibrations obtained after the installations by different methods. We illustrate short‐term strain changes recorded during several lava fountains erupted by Etna during 2011–2013, and we also show signal changes recorded at all four stations during the lava fountain on 28 December 2014. Analytical and numerical computations constrained the eruptions source depth and also its volume change that is related to the magma volume emitted. Finally, we show the potential of the signal in the medium term to reveal strain changes related to different phases of the volcanic activity. Key Points: New borehole dilatometer network on Etna volcano Strain changes tracing lava fountain eruptions and volcano phases Eruption sources modeling and eruptive mechanisms inferring